Teaching Speaking Skill By Using Numbered Head Together - Yunita Sari; Usman Kasim; Chairina Nasir (Universitas Syiah Kuala, 2021)
This research was conducted at SMPN 3 Gunung Meriah, Aceh Singkil. It was intended to find out whether the use of Numbered Head Together improved students’ speaking ability in learning speaking or not. The researcher used random sampling by drawing lottery number. The sample of this research was the students of grade VIII-1. The data was collected by researcher using pre-test, treatment and post-test. The materials used in the speaking tests were pictures. The speaking aspects were pronunciation, grammar, vocabulary, fluency and comprehension. In analyzing the data, the researcher used statistical formula. The mean score of pre-test was 45 and post-test was 70. The data showed that the improvement of the mean was 25. The critical value of 0.05 significant level and 19 degree of freedom was 2.093. The result of t-test (3.930) was higher than t-table (2.093). So, this mean that the implementation of teaching speaking skill by using Numbered Head Together give significant difference in students speaking scores between pre-test and post-test of students VIII-1 of SMPN 3 Gunung Meriah.